Active Fractions of Black Rice Bran cv Cempo Ireng Inducing Apoptosis and S-phase Cell Cycle Arrest in T47D Breast Cancer Cells - Rarastoeti Pratiwi; Alfi Rizqi Amalia; Woro Anindito Sri Tunjung; Rumiyati Rumiyati (Institute for Research and Community Services (LPPM) ITB, 2019)
Indonesian black rice cv Cempo Ireng was evaluated for cancer prevention using a T47D cell line model. Methanolic extract of black rice bran (BRB) showed cytotoxicity with an IC50 of 522.13 µg/ml. This result was in contrast to water extract of BRB, which yielded an IC50 of more than 6000 µg/ml. From the methanolic extract of BRB, its 6 fractions were found from the preparative TLC performance, with Rf values ranging from 0 to 0.97. According to the MTT assay of all fractions, fraction 3 (F3) had the lowest IC50 (60.17 ± 1.72µg/ml), while fraction 2 (F2) had an IC50 of 64.3 ± 0.61µg/ml. However, F2 showed the highest induction of apoptosis, i.e. about 75.39 ± 0.43% compared to the T47D cells without treatment (control) (about 8.39 ± 0.16%) and with doxorubicin treatment (about 41.30 ± 0.08%). Furthermore, fraction 5 (F5) not only induced apoptosis but also increased the S-phase arrest percentage (60.36 ± 2.07%), which was significantly higher than for the other treatments. Therefore, each fraction of BRB showed different cytotoxic responses to T47D cells.